DyNet-LCCA: a simulation framework for dynamic network-level life- cycle cost analysis in evolving infrastructure systems. Issue 2 (4th March 2022) - Batouli, Mostafa; Mostafavi, Ali; Chowdhury, Arindam G.
ABSTRACT: Civil infrastructure systems transform over the long-term due to complex interactions among socio-environmental stressors, degradation of physical networks, and decision-making processes of infrastructure agencies. To incorporate such complex transformation mechanisms into infrastructure cost management, this study integrates simulation modeling and life-cycle cost analysis (LCCA) to create a framework for dynamic network-level LCCA in infrastructure systems. The proposed framework was implemented using a multi-agent simulation model in a numerical case study related to a road network affected by sea-level rise, population growth, and uncertain maintenance funding. The results include identification of several state transition, and tipping point behaviors at which small changes in service demand, maintenance budget, and adaptation investment may result in significant improvement in network cost and performance conditions. The results show the capability of the proposed framework in modeling the long-term trajectories of life-cycle costs at the network level under different stressors and decision scenarios.